Borate Bioactive Glasses (BBG): Bone Regeneration, Wound Healing Applications, and Future Directions - Ege, Duygu; Zheng, Kai; Boccaccini, Aldo R. (ACS Applied Bio Materials, 2022)
Since the early 2000s, borate bioactive glasses (BBGs) have been extensively investigated for biomedical applications. The research so far indicates that BBGs frequently exhibit superior bioactivity and bone healing capacity compared to silicate glasses. They are also suitable candidates as drug delivery devices for infection or disease treatment such as osteoporosis. Additionally, BBGs are also an excellent option for wound healing applications, which includes the availability of commercial (FDA approved) microfibrous BBG dressings to treat chronic wounds. By addition of modifying ions, the bone or wound healing capacity of BBGs can be enhanced. For instance, addition of copper ions into BBGs was shown to drastically increase blood vessel formation for wound healing applications. Moreover, addition of ions such as magnesium, strontium, and cobalt improves bone healing. Other recent research interest related to BBGs is focused on nerve and muscle regeneration applications, while cartilage regeneration is also suggested as a potential application field for BBGs. BBGs are commonly produced by melt-quenching; however, sol-gel processing of BBGs is emerging and appears to be a promising alternative. In this review paper, the physical and biological characteristics of BBGs are analyzed based on the available literature, the applications of BBGs are discussed, and future research directions are suggested.
CRIS-Team WoS Importer:2022-08-05